Interpretational oppositions between the majority opinion of the court and the dissenting opinion - Wojciechowski, Maciej (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2023)
This article aims to identify the reasons for disagreement in interpretive judgments by examining selected cases from the Polish Supreme Administrative Court. The analysis focuses on the traditional triad of linguistic, systemic, and teleological interpretive can- ons. The study distinguishes interpretive disputes in a weak and strong sense (axiological disputes) and explores the utilisation of interpretive canons in the examined cases. The values used to characterise specific interpretive positions do not necessarily align with the intended purposes of the interpreted provisions. The analysis of opposing opinions, initially expected to reveal easily describable interpretive oppositions, proved challeng- ing due to the complex nature of argumentation used to justify positions. While classic opposition between linguistic and teleological rationales was occasionally observed, it was difficult to discern such oppositions solely based on the justifications provided. In conclusion, the article tentatively posits that interpretive canons serve a more justificato- ry than heuristic function, providing limited explanation for occurrence of interpretive disagreements.
Keywords: ločena mnenja; nesoglasja; Poljska; razlaga pravnih aktov; razlagalne sodbe; sodišča